(untitled) (Heritage, 2021)
The Gulf War represents a turning point in understanding of psychological warfare, so as the way of presenting development of war in the media. The basic means are not propagandas’ messages and leaflets, anymore. The chosen reporters, the chosen journalists and the chosen TV stations have primacy. The development of technique and technology and apperapance of social network services and applications creates posibillity for avoidnig of war in classical meaning. The classic armed conflict creates huge economic consequences and political crysis with longterm effects. Becouse of it, the basic mean of fight in psychological warfare becomes disinformations and missinformations. Their ability of quick and efficient adaptation for modern technologies demands brings to the evolution into another modes of psychological warfare, such as spinn, fake news, astroturfing, social engineering. Traped into their own pitfall becouse of fight for market by their insisting on interactivity with their readers and audience, the media give possibility for creating fake, made up public opinion. For now, there are two possible solutions for this situation: by canceling of access to the interactive contents either by ignoring true facts if they are not compatible with the policy of certain media or redaction (if it was shown that older course of reporting was not auspicious for them of was not true from the very beginning).